2018
DOI: 10.24853/jkk.14.2.21-30
|View full text |Cite
|
Sign up to set email alerts
|

Faktor yang Berhubungan dengan Hipertensi pada Ibu Hamil di Kota Makassar

Abstract: Hipertensi mer upakan salah satu masalah kesehatan yang sering muncul selama kehamilan dan dapat menimbulkan komplikasi pada 2-3% kehamilan. Penelitian ini bertujuan mengetahui faktor yang berhubungan dengan kejadian hipertensi pada ibu hamil di wilayah kerja Puskesmas Kassi-kassi Kota Makassar. Penelitian ini merupakan penelitian observasional analitik dengan desain cross sectional. Populasi dalam penelitian ini adalah seluruh ibu hamil di wilayah kerja Puskesmas Kassi-kassi Kota Makassar yang tercatat pada b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
0
0
1
3
Order By: Relevance
“…The results of this study are also in line with research conducted in West Java Province which stated that there was no relationship between the consumption of saturated fatty foods and the incidence of gestational hypertension with a p-value of 0.601 15 . However, this is different from research conducted in Makassar City which stated that there was a significant relationship between the consumption of saturated fatty foods and the incidence of gestational hypertension with a p-value of 0.000 16 . The results of research conducted in DKI Jakarta states that there is no relationship between consumption of saturated fatty foods and the incidence of gestational hypertension with a p-value of 0.323 17 .…”
Section: Relationship Between Risk Factors and The Incidence Of Gesta...contrasting
confidence: 91%
“…The results of this study are also in line with research conducted in West Java Province which stated that there was no relationship between the consumption of saturated fatty foods and the incidence of gestational hypertension with a p-value of 0.601 15 . However, this is different from research conducted in Makassar City which stated that there was a significant relationship between the consumption of saturated fatty foods and the incidence of gestational hypertension with a p-value of 0.000 16 . The results of research conducted in DKI Jakarta states that there is no relationship between consumption of saturated fatty foods and the incidence of gestational hypertension with a p-value of 0.323 17 .…”
Section: Relationship Between Risk Factors and The Incidence Of Gesta...contrasting
confidence: 91%
“…This is in line with research conducted by on factors related to hypertension in pregnant women in the city of Makassar. The results showed that education had no significant relationship between education and hypertension in pregnant women, as evidenced by the acquisition of a p value of 0.615 (Basri et al, 2018).…”
Section: The Relationship Between Education and Hypertension In Pregn...mentioning
confidence: 87%
“…Pada ibu hamil yang terpapar stres psikologi didapatkan terjadi peningkatan konsentrasi serum biomarker inflamasi (interleukin (IL) -6, tumor necrosis factorα (TNF-α), dan CRP) yang dapat menyebabkan prematur dan meningkatkan kejadian hipertensi (Caplan et al, 2021) dan Suef (2016). Pada studi yang dilakukan oleh Basri et al (2018) menemukan bahwa stres dapat meningkatkan tekanan darah menjadi tinggi yang dpat menyebabkan terjadinya hipertensi, Ini bisa terjadi karena stres meningkatkan saraf simpatis, yang bisa meningkatkan tekanan darah (Basri et al, 2018) Faktor hipertensi gestasional menyebabkan stres/kecemasan [1, 8, dan 10] Ibu hamil yang terdiagnosa hipertensi gestasional mengalami perubahan psikologi, yang ditandai dengan munculnya perasaan takut, terkejut dan bersalah ibu hamil menggambarkan perasaan mereka dengan tidak siap dan membutuhkan waktu dalam menerima keadaan mereka. Perasaan bersalah, perubahan rencana kehamilan dan persalinan dan kemungkinan melahirkan bayi prematur, menyebabkan distres psikologi pada ibu hamil dengan hipertensi gestasional, hal ini ditandai dengan perubahan kualitas tidur, dan mood ibu hamil yang sering berubah-ubah (Roberts et al, 2017).…”
Section: Pembahasan Faktor Stres/kecemasan Menyebabkan Hipertensi Ges...unclassified